2022
DOI: 10.3390/ijms23073977
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Represses Thymic Stromal Lymphopoietin Gene Expression through Activation of Glucocorticoid Receptor and Protein Kinase C Delta in Inflamed Skin Keratinocytes

Abstract: Ghrelin, a peptide hormone secreted from enteroendocrine cells of the gastrointestinal tract, has anti-inflammatory activity in skin diseases including dermatitis and psoriasis. However, the molecular mechanism underlying the beneficial effect of ghrelin on skin inflammation is not clear. In this study, we found that ghrelin alleviates atopic dermatitis (AD)-phenotypes through suppression of thymic stromal lymphopoietin (TSLP) gene activation. Knockdown or antagonist treatment of growth hormone secretagogue re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 112 publications
0
1
0
Order By: Relevance
“…The injection of antibodies against TSLP in psoriasis-like mouse models has resulted in the regression of psoriasis, reduced epidermal hyperplasia, decreased VEGF α expression, and the epidermal inhibition of STAT-5 phosphorylation [236]. One of the possible directions of therapeutic strategies is the suppression of TSLP gene activation by ghrelin, which acts through the activation of glucocorticoid receptors [237]. Tashiro et al, studying the effects of hypoxia on TSLP, found an inhibition of the TNF-α -induced expression of TSLP in human and mouse keratinocyte cell lines.…”
Section: Thymic Stromal Lymphopoietinmentioning
confidence: 99%
“…The injection of antibodies against TSLP in psoriasis-like mouse models has resulted in the regression of psoriasis, reduced epidermal hyperplasia, decreased VEGF α expression, and the epidermal inhibition of STAT-5 phosphorylation [236]. One of the possible directions of therapeutic strategies is the suppression of TSLP gene activation by ghrelin, which acts through the activation of glucocorticoid receptors [237]. Tashiro et al, studying the effects of hypoxia on TSLP, found an inhibition of the TNF-α -induced expression of TSLP in human and mouse keratinocyte cell lines.…”
Section: Thymic Stromal Lymphopoietinmentioning
confidence: 99%
“…In vitro experiments demonstrated that the TSLP expression is significantly elevated in TNF- α -inflamed HaCaT [ 43 ] and ploy (I:C)-induced NHEK cells [ 44 ]. Recent studies hinted that keratinocyte-expressed TSLP is upregulated via TLR [ 45 ] and histamine 4 receptor [ 46 ] while negatively regulated through glucocorticoid receptor [ 47 ] and aryl hydrocarbon receptor [ 48 ]. Furthermore, Yoo et al engineered a kind of transgenic mice (K5-TLSP transgenic mice) that overexpress tetracycline-inducible TSLP in keratinocytes under the control of the keratin 5 promotor [ 49 ].…”
Section: Tslp Role During Ad Pathogenesismentioning
confidence: 99%